FAKE NEWS, THE EFFECTS OF SOCIAL MEDIA - Xoldarova Sarvinoz; To’raxon Abduraxmonov (TADQIQOTLAR, 2025)
Annotation:This text examines the growing influence of fake news and social media on modern society. It begins by defining fake news and explaining its various forms, such as fabricated stories, misleading content, manipulated visuals, and satire taken  out  of  context.  The  text  highlights  the  severe  social  consequences  of misinformation, including fear, distrust, political manipulation, damaged reputations, and  threats  to  public  health.  It  then  explores  the  positive  impact  of  social  media, including improved communication, educational opportunities, business development, and  community  building.  At  the  same  time,  it  presents  the  darker  side  of  social platforms—addiction,  reduced  productivity,  mental  health  issues,  cyberbullying, privacy risks, and unrealistic social comparison. The text also explains why fake news spreads rapidly, noting psychological biases, economic motives, political agendas, and advanced technologies like deepfakes. In conclusion, the author emphasizes that while digital tools can be powerful, their impact depends largely on users’ responsibility, critical thinking, and awareness. By making informed choices, society can harness technology for unity, truth, and progress rather than division and deception.